Hubungan Pengetahuan Kesiapsiagaan Bencana Banjir Dengan Tingkat Kecemasaan Masyarakat Di Kelurahan Wonasa Tanjung - Sri Wahyuni Misaala; Sunarti Basso; Faradilla M. Suranata (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Flooding is an event or event that results in the submergence of an area or land due to an increased volume of water. Flooding is caused by climate change, lack of water reception upstream area due to the many buildings, residential houses on the banks of the river and the lack of public awareness to maintain the cleanliness of the river. Flood disasters have a negative impact on individuals, communities and the environment. For individuals can be at risk of drifting, injuries, injuries, to other health problems such as digestive disorders, skin diseases, to infections. This impact can be reduced by improving community preparedness in facing disasters. All activities are carried out to anticipate disasters through organizing and using appropriate scarce disaster management in the preparedness phase. The purpose of this study is to determine whether there is a relationship between flood preparedness knowledge and the level of community anxiety in Wonasa Tanjung Village. This research was conducted with Descriptive Analytic method with Cross Sectional approach. There were 106 Subjekts. Data collection is carried out using questionnaires. Furthermore, the data was analyzed with the Chi-squaer test with a meaning level (a).0.05. The results of the study using the Chi-squere statistical test obtained a p value Value = 0.01 where the p Value value <a = 0.05 The results of this study show that there is a relationship between flood disaster preparedness knowledge and the level of anxiety of the community in Wonasa Tanjung Village. The conclusion of this study is that there is a relationship between flood disaster preparedness knowledge and the level of community anxiety in Wonasa Tanjung Village. Advice for the Wonasa Tanjung environment is to maintain cleanliness and no longer throw rubbish in the river.